1999
DOI: 10.1002/(sici)1097-0142(19990315)85:6<1261::aid-cncr7>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

An investigational new drug treatment program for patients with gemcitabine

Abstract: BACKGROUND An Investigational New Drug (IND) treatment program allows patients access to a drug that has shown activity against a serious or life‐threatening disease prior to full Food and Drug Administration (FDA) review and approval. This treatment IND program, in which patients with locally advanced or metastatic pancreatic carcinoma were treated with gemcitabine, began in 1995. METHODS Eligibility criteria were ≤1 prior chemotherapy regimen; a Karnofsky performance status (KPS) of ≥50; and adequate bone ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
0
5

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(80 citation statements)
references
References 11 publications
3
72
0
5
Order By: Relevance
“…Gemcitabine, the best chemotherapeutic agent available for the treatment for advanced pancreatic cancer, alone is not very eVective and is associated with systemic toxicity and chemoresistance (Storniolo et al 1999;Moore et al 2007;Diaz-Rubio 2004). It was still unknown whether escin could potentiate the antitumor activity of gemcitabine against pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Gemcitabine, the best chemotherapeutic agent available for the treatment for advanced pancreatic cancer, alone is not very eVective and is associated with systemic toxicity and chemoresistance (Storniolo et al 1999;Moore et al 2007;Diaz-Rubio 2004). It was still unknown whether escin could potentiate the antitumor activity of gemcitabine against pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical benefit response, however, can underestimate the effects of chemotherapy because it does not include the assessment of other symptoms. Furthermore, it can overestimate the results of chemotherapy, the reason for this being that it does not properly assess the side effects [75,76]. Therefore, quality of life (QOL) studies have been introduced in the latest adjuvant clinical trials.…”
Section: Survival Statistics and Definition Of Endpoints In Pancreatimentioning
confidence: 99%
“…Through several phase III trials, GEM has been indicated as a first-line treatment for patients with advanced pancreatic cancer including metastatic tumor, because it improves survival [28] and has clinical advantages (pain reduction, improved performance status, weight gain) over 5-FU treatment [6,19].…”
Section: Introductionmentioning
confidence: 99%